Improving the English Skills of Elementary School Students in Tourism Areas - Azizah, Siti Nur; Setiadi, Muhammad Randi; Agusman, Desi Destiana; Raprap, Faino Elesion (Buletin KKN Pendidikan, 2023)
English is an international language used by the global community from various countries to communicate with each other by default. However, not all people living in tourism areas, including schoolchildren, have fluent English skills. Even though school children are the next generation, who will later develop tourism potential in the area, this service provides English language training to elementary school students in potential tourism areas in Belitung Regency. The community service method is in the form of pronunciation training and short conversations in English, delivered in English games and songs. As a result, children become more proficient in vocabulary and communicating briefly in English. The results of this study indicate that children can quickly master foreign languages if their learning is in the form of fun games or songs. So that English skills can begin to be applied to children and later will make it easier for them to communicate with foreign tourists who stop at these tourist sites.